Comparative effects of unilateral and bilateral plyometric training on physical fitness in adolescent team-sport athletes: a systematic review and meta-analysis - Zhang, F.; Liu, Y.; Shi, S.; Wang, H.; Liu, J.; Yeremenko, O. (Frontiers in Physiology, 2026)
Objective: This study aimed to compare the relative effects of unilateral and bilateral plyometric training on jump, sprint, and change-of-direction performance in adolescent team-sport athletes.